2003
DOI: 10.1891/vivi.2003.18.5.581
|View full text |Cite
|
Sign up to set email alerts
|

Violence Against Women With Physical Disabilities

Abstract: This study explored risk factors for violence among a sample of adult women with physical disabilities. Fifty-six percent (100) of the 177 women participating in the study indicated a positive history of abuse. Of the women who reported abuse, most reported multiple abuse situations and abusers who were typically their male partners. In addition, only a small proportion of women sought and received adequate help. Women who indicated that they did not seek help were asked why this was the case. Their responses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
61
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 49 publications
(62 citation statements)
references
References 11 publications
1
61
0
Order By: Relevance
“…Four studies [Nosek, 1995;Young et al, 1997;McFarlane et al, 2001;Milberger et al, 2003] focused on prevalence of maltreatment among women with physical disabilities. Nosek [1995] described a qualitative study carried out by the Center for Research on Women with Disabilities (CROWD).…”
Section: Summary Of Studies and Findingsmentioning
confidence: 99%
See 4 more Smart Citations
“…Four studies [Nosek, 1995;Young et al, 1997;McFarlane et al, 2001;Milberger et al, 2003] focused on prevalence of maltreatment among women with physical disabilities. Nosek [1995] described a qualitative study carried out by the Center for Research on Women with Disabilities (CROWD).…”
Section: Summary Of Studies and Findingsmentioning
confidence: 99%
“…In one of the rare adult prevalence studies to utilize a comparison group, Young et al [1997] surveyed 504 women with disabilities recruited through Centers for Independent Living and media announcements and asked them to pass on a survey to a nondisabled female friend, resulting in a comparison group of 442 women without disabilities. About 62% of the women Milberger, [2003] 177 X X X X X X X X X Nosek, [1995] 31 X X X X X X X X X Oktay and Tompkins [2004] 84 X X X X X X X X X X X Suris et al [1996] 2,961 X X X X X X X X Svetaz et al [2000] 16,240 X X X X X X X X X Young et al [1997] 846 X X X X X X X X X in both groups reported that they had experienced some type of abuse at some point in their lives. Women with and without disabilities did not differ significantly in the proportions that had experienced emotional (51.7 versus 47.5%), physical (35.5 versus 35.6%), or sexual abuse (39.9 versus 37.1%), but women with disabilities had experienced abuse for significantly longer periods of time than women without disabilities.…”
Section: Summary Of Studies and Findingsmentioning
confidence: 99%
See 3 more Smart Citations